The diet of the Burrowing Owl, Athene cunicularia, in the arid lands of northeastern Patagonia, Argentina - Nabte, Marcela Janina (2008)
We studied the diet of the Burrowing Owl (Athene cunicularia) through 1-year pellet analysis in the southern portion of the Monte Desert, Patagonia. The pellets were collected in Protected Natural Area Península Valdés, Chubut, Argentina. We identified 3787 individual prey items belonging to 19 prey species in 589 pellets analyzed and we found a mean of 1.36±0.65 vertebrate individuals (range=1-4) per pellet. Insecta were the main prey items accounting for 51.9% of individuals consumed, followed by Chelicerata (25.3%) and Mammalia (20.9%). However, the greatest contribution of biomass to owl diets came from the consumption of small rodents (94.4%). Our results suggest that the Burrowing Owl were mainly nocturnal hunters and evidenced a generalist diet, consuming a wide spectrum of prey items, including invertebrates (insects and chelicerates), and several types of vertebrates (mammals, birds and lizards).